Association between bibliometric parameters, reporting and methodological quality of randomised controlled trials in vascular and endovascular surgery. (April 2017) - Hajibandeh, Shahab; Hajibandeh, Shahin; Antoniou, George A; Green, Patrick A; Maden, Michelle; Torella, Francesco
Purpose: We aimed to investigate association between bibliometric parameters, reporting and methodological quality of vascular and endovascular surgery randomised controlled trials. Methods: The most recent 75 and oldest 75 randomised controlled trials published in leading journals over a 10-year period were identified. The reporting quality was analysed using the CONSORT statement, and methodological quality with the Intercollegiate Guidelines Network checklist. We used exploratory univariate and multivariable linear regression analysis to investigate associations. Findings: Bibliometric parameters such as type of journal, study design reported in title, number of pages; external funding, industry sponsoring and number of citations are associated with reporting quality. Moreover, parameters such as type of journal, subject area and study design reported in title are associated with methodological quality. Conclusions: The bibliometric parameters of randomised controlled trials may be independent predictors for their reporting and methodological quality. Moreover, the reporting quality of randomised controlled trials is associated with their methodological quality and vice versa.